Dramatisation as a strategy in teaching aural-oral skills to learners in a rural primary school / Asma Ahmad - Ahmad, Asma (2014)
This case study investigates if techniques of dramatisation could be an effective strategy in teaching aural/oral skills among Year Six learners in a rural national primary school in Sungai Leman, Sekinchan, Sabak Bernam district in Selangor. The sample for this study was 50 Year Six learners. This study was designed to find out whether the use of dramatisation via a drama workshop is effective in improving the aural-oral skills of the sample. Both qualitative and quantitative methods were adopted in the study. The qualitative investigation covered evaluation of attitudes, perceptions and behaviour while the quantitative portion involve the generation of statistical data analysis from the results of their pre and post-test of the School Based Oral Assessment. The purpose of the study was to use the drama workshop as a remedy to help these learners speak English in order to help them improve their oral test scores. During the drama workshop, they learned to speak and communicate in English using puppets and other props. The samples participated actively in the drama activities and participated in listening and speaking games which they had not experienced in their classroom before. The analysis of the findings from the research instruments used; survey questionnaires, observation, interviews and written journal feedback revealed that the learners were more confident and not afraid of making mistakes when speaking English. They created puppets and stories to role play in the classroom with props. The paired sample t-test used to measure the difference between the oral pre and post-tests revealed a significant difference between the pre and post-tests scores establishing a relationship between the achievement of learners and the use of ‘Dramatisation’ as a learning strategy in the enhancement of aural-oral skills.